Development of an efficient timetable system using angularjs and bootstrap 3 - Perumal S.A.L.; Tabassum M.; Norwawi N.M.D.; Samy G.A.L.N.; Perumal S.A.L. (Institute of Electrical and Electronics Engineers Inc., 2024)
Managing subjects', lectures and classroom are complex issues in Universities and learning institutions. Programs, subjects' management and timetabling are hectic and time consuming tasks which create multi-dimensional and highly constrained issues in learning institutions. Creating educational timetable manually required a lot of time, several resources and numerous rounds of changes before it has been finalized. Assigning multiple subjects to one lecturer and allocating multiple classroom for different subjects are tough tasks as well and need a solid framework and comprehensive solution. Automatic generation of timetable is an attractive approach as compared to a manual approach. Many applications are available in the industry for this purpose. However, they are expensive in price and charged huge licensing cost yearly. Therefore, in this paper, we are developing a specific timetabling application using open source frameworks. We have used AngularJS, Bootstrap 3, and PHP along other frameworks to design and develop an automatic timetable system which has a graphical user friendly and attractive interface. The developed system has a flexible representation and appropriate methods to create a feasible, automatic timetable and avoid clashes. The system is implemented and tested to create timetables for the Faculty of Science and Technology at Universiti Sains Islam Malaysia (USIM). 2018 IEEE.